af014606: Vietnam vencera / Day of international solidarity with the people of Zimbabwe - Beltrán Concepción, Félix; Mederos Pazos, René; Organization of Solidarity with the People of Asia, Africa and Latin America (1968)
"Affiche ontworpen door Félix Beltrán (recto) en René Mederos (verso), uitgegeven in 1968 door de Organization of Solidarity with the People of Asia, Africa and Latin America (OSPAAAL) voor solidariteit met de Vietnamezen en de Zimbabwanen. Afbeelding recto: tekening van in elkaar gehaakte kleurvlakken. Tekst recto: VIETNAM VENCERA. VIETNAM WILL WIN. VIETNAM VAINCRA. JORNADA MUNDIAL DE SOLIDARIDAD CON VIETNAM. INTERNATIONAL DAY OF SOLIDARITY WITH VIETNAM. JOURNEE MONDIALE DE SOLIDARITE AVEC LE VIETNAM. COMITE TRICONTINENTAL DE APOYO A VIETNAM 20 DE DICIEMBRE. TRICONTINENTAL COMMITTEE OF SUPPORT TO VIETNAM DECEMBER 20th. COMITE TRICONTINENTAL D'APPUI AU VIETNAM 20 DECEMBRE. Afbeelding verso: foto van een zwarte man die werd opgepakt door blanke politieagenten. Tekst verso: DAY OF INTERNATIONAL SOLIDARITY WITH THE PEOPLE OF ZIMBABWE september 12. OSPAAAL. FULL TEXT AVAILABLE AT AMSAB-ISH"